Orbital evolution of the mu and nu dust ring particles of Uranus - Sfair, R. [UNESP]; Winter, S. M. Giuliatti [UNESP] (Edp Sciences S A, 2009)
The mu and nu rings of Uranus form a secondary ring-moon system with the satellites Puck, Mab, Portia, and Rosalind. These rings are tenuous and dominated by micrometric particles, which can be strongly disturbed by dissipative forces, such as the solar radiation pressure. In the region of these rings, the solar radiation force and the planetary oblateness change the orbital evolution of these dust particles significantly. In this work, we performed a numerical analysis of the orbital evolution of a sample of particles with radii of 1, 3, 5, and 10 mu m under the influence of these perturbations, combined with the gravitational interaction with the close satellites. As expected, the Poynting-Robertson component of the solar radiation force causes the collapse of the orbits on a timescale between 3.1 x 10(5) and 3.6 x 10(6) years, while the radiation pressure causes an increase in the eccentricity of the particles. The inclusion of Uranus's oblateness prevents a large variation in the eccentricity, confining the particles in the region of the rings. The encounters with the close satellites produce variations in the semimajor axis of the particles, leading them to move inward and outward within the ring region. These particles can either remain within the region of the rings or collide with a neighbouring satellite. The number of collisions depends on the size of both the particles and the satellites, and the radial width of the ring. For the time span analysed, the percentage of particles that collide with a satellite varies from 43% to 94% for the. ring, and from 12% to 62% for the mu ring. Our study shows that all collisions with Portia and Rosalind have the value of impact velocity comparable to the escape velocity, which could result in the deposition of material onto the surface of the satellite. Collisions between Puck and particles larger than 1 mu m also occur at an impact velocity comparable to the value of the escape velocity. The exception is Mab, which is hit by particles with velocities several times larger than the escape velocity. These collisions are energetic enough to eject material and supply material to the mu ring. However, only a few particles (3%) collide with the surface of the satellite Mab at such a velocity.
Keywords: planets: rings; planets and satellites: individual: Uranus; methods: N-body simulations